Arsenic contamination of groundwater and its health impact on residents in a village in West Bengal, India - Rahman Mohammad Mahmudur; Sengupta Mrinal Kumar; Ahamed Sad; Chowdhury Uttam Kumar; Lodh Dilip; Hossain Amir; Das Bhaskar; Roy Niladri; Saha Kshitish Chandra; Palit Shyamal Kanti; Chakraborti Dipankar (Bulletin of the World Health Organization, 2005)
An in-depth study was carried out in Rajapur, an arsenic-affected village in West Bengal, India, to determine the degree of groundwater contamination with arsenic and the impact of this contamination on residents. The flow injection hydride generation atomic absorption spectrometry (FI-HG-AAS) method was used to measure arsenic concentrations in water and biological samples. Dermatologists recorded the dermatological features of arsenicosis. Out of a total of 336 hand-pumped tube-wells in Rajapur, 91% (307/336) contained arsenic at concentrations > 10 mg/l, and 63% (213/336) contained arsenic at > 50 mg/l. The type of arsenic in groundwater, the variation in concentrations of arsenic as the depth of tube-wells changed, and the iron concentration in the wells were also measured. Altogether 825 of 3500 residents were examined for skin lesions; of these, 149 had lesions caused by exposure to arsenic. Of the 420 biological samples collected and analysed, 92.6% (389) contained arsenic at concentrations that were above normal. Thus many villagers might be subclinically affected. Although five arsenic-filtering devices had been installed in Rajapur, it appears that villagers are still exposed to raised concentrations of arsenic in their drinking-water. Detailed village-level studies of arsenic-affected areas in West Bengal are required in order to understand the magnitude of contamination and its effects on people. Villagers are ill-informed about the dangers of drinking arsenic-contaminated water. The contamination could be brought under control by increasing community awareness of the dangers and implementing proper watershed management techniques that involve local people.